SOSIALISASI PERMAINAN GROS MOTORIK UNTUK ANAK USIA DINI - Kartini Kartini; Kurnia Dyah Anggorowati; Kasihani Lestari (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Gross motor movements are abilities that require coordination of most parts of a child's body. Gross motor movements require energy because they are carried out by larger muscles. In general, learning in PAUD is more focused on the development of fine motor aspects, while gross motor development is given less attention. Development of gross motor aspects in early childhood such as throwing and catching balls, walking on catwalks, walking with various variations, jumping and so on. These activities are rarely practiced by young children, under the guidance and supervision of educators or teachers, and it is hoped that all aspects of development can develop optimally. The aim of this community service is to improve the skills and understanding of PAUD teachers in Nanga Pinoh sub-district, Melawi district. creating games that can improve children's gross motor development. This service activity is motivated by identified partner weaknesses including (1) variations in carrying out gross motor activities so that children are reluctant to take part in physical learning, (2) gross motor skills have not grown optimally, this causes children to lack practice in physical learning activities, (3 ) reference books and information about gross skills are not yet widely owned by PAUD teachers so that the learning process only refers to the teacher's experience, (4) Lack of innovation by teachers in providing teaching methods through games that can improve children's physical development. The solution offered is to provide Socialization of Gross Motor Games for Early Age Children, Nanga Pinoh District, Melawi Regency. The external target of this penandian is socialization and assistance in gross motor games for PAUD teachers and children which is held for two days. The methods used are lecture, simulation and discussion methods. The result of implementing this community service activity is to provide an overview and direction to teachers that playing educational games can improve aspects of children's development, especially gross motor development. Educational outdoor games provide opportunities for children to learn cooperation, solidarity, tolerance, honesty, discipline, hard work, increase creativity, independence, democracy, curiosity, national spirit, respect, leadership, cooperation, care for the environment, caring. social, responsibility, religious, and likes to read. Based on these conditions, it is necessary to carry out community service activities as one of the implementations of the Tri Darma of Higher Education activities. This service activity was carried out for children and PAUD teachers in Nanga Pinoh District, Melawi Regency. The teacher is responsible for the success of every learning activity that has been designed. Teachers who are not optimal in preparing game designs will produce learning activities that are not optimal. This causes the targeted learning achievements not to be achieved.Keywords: Socialization, Gross Motor Games, Early Childhood